Import protection, capital flows, and real exchange rate dynamics - Sjaastad, L.; Manzur, Meher (Universidad del CEMA, 2003)
This paper focuses on the effect of import protection on the response of the real exchange rate to capital flows. The central hypothesis is that barriers to imports blunt the expenditure and production shifting effects of changes in relative prices, and hence the ability of the real exchange rate to equilibrate the economy in response to international capital flows. Employing a cross-secion approach, the study focuses on three broadly similar countries but with very different levels of protection: Argentina, Australia, and Canada. The empirical results are consistent with the central hypothesis.